2018
DOI: 10.18203/2320-1770.ijrcog20181978
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stress urinary incontinence and its associated risk factors amongst females attending tertiary referral centre

Abstract: Background: Urinary incontinence (UI) is one of the most common diseases in the world, occurring majorly in females. The most common reason of its occurrence in women is: stress urinary incontinence. The frequent and repeated small leaks lead to soreness and excoriation of the vulva, and necessitate frequent changes of underclothing or the constant wearing of the protective clothing. In severe cases the woman’s life becomes a misery; she feels a social outcast and avoids leaving the house.Methods: This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…11 The latest research in India in 2018 from 418 cases, found 77 cases (18.4%) having SUI. 12 The prevalence rate of SUI in this study was lower because IU was considered a taboo and embarrassing thing to talk about and to tell doctors, so it is often not reported by patients or their families. Because there is an assumption that the problem is a shameful thing, so there is no good record made.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…11 The latest research in India in 2018 from 418 cases, found 77 cases (18.4%) having SUI. 12 The prevalence rate of SUI in this study was lower because IU was considered a taboo and embarrassing thing to talk about and to tell doctors, so it is often not reported by patients or their families. Because there is an assumption that the problem is a shameful thing, so there is no good record made.…”
Section: Resultsmentioning
confidence: 59%
“…This result is the same as the study at India in 2018 by Gita et al which reported an increase in the number of SUI at age > 60 by 83.3% and age 40-60 by 51.81%. 12 IGPSuka Aryana et al in the 2018 Geriatric Opinion also reported that SUI was 22% suffered by women aged between45-64 years. 15 In general, women of menopausal age will experience hormonal, physical and psychological changes.…”
Section: Resultsmentioning
confidence: 99%
“…11 As far as demographic, anthropometric and comorbidity profile of cases in present study is concerned it is similar to that reported by Guin et al who also highlighted age group 40-60 years, higher BMI, and associated comorbidities to be common characteristics of the patients. 12 In present study, pre-treatment general health/incontinence impact, quality of life and symptom scores (Parts 1, 2 and 3 of King's Health Questionnaire) were 123.00±48.47, 247.94±115.08 and 16.50±6.25 respectively which declined to reach at 32.99±36.76, 50.01±66.27 and 3.56±4.78 respectively at follow-up, thus showing % decline of 73.2%, 79.8% and 78.4%. A total of 27 (54%) were entirely symptom free at one-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This risk increased with assisted delivery and perineal laceration. 20,23,24 Roetviet G et al also reported that the risk of urinary incontinence is higher among women who have had cesarean sections than among nulliparous women and is even higher among women who have had vaginal deliveries.…”
Section: Instrumental Deliverymentioning
confidence: 99%
“…Minassian VA et al reported that the prevalence of SUI peaked at the fifth decade. 20,21 Hijaz A et al concluded that the advanced maternal age clearly represents an independent risk factor for postpartum SUI. 22…”
Section: Risk Factors Of Sui Agementioning
confidence: 99%